Effect of Carcass Size on Feeding Modes of Larvae of Nicrophorus quadripunctatus Kraatz (Coleoptera: Silphidae) - Ryu Kishida; Nobuhiko Suzuki (Psyche: A Journal of Entomology)
In the parental care of burying beetles of Nicrophorus, the role of males has not been clearly elucidated. To test our hypothesis that the investment in resource manipulation by males influences the feeding of larvae by males, we investigated parental efforts of N. quadripunctatus. On the small carcasses, the time spent on resource manipulation by males was short, and the males left the carcasses without feeding the larvae (maternal feeding). On the large carcasses, the males spent a long time on resource manipulation, and the male participated in the feeding of larvae (biparental feeding). This suggests that one of the reproductive roles of males in the absence of predators and/or competitors is resource manipulation, and the paternal efforts change depending on carcass size. A longer time spent on resource manipulation by males may be a trigger for the males to participate in the feeding of larvae on large carcasses.